Structural Breaks and Volatility Spillover in South Asian Economies - Hafiz Rauf Iqbal; Syed Kashif Saeed; Syed Zulfiqar Ali Shah (SEISENSE Journal of Management, 2020)
Purpose - This study examines the volatility spillovers in the presence of structural breaks with specific reference to South Asian Capital markets. The global financial crisis of 2007-2009 has compelled policymakers to realize that financial instability has the potential to threaten economic stability and growth; therefore, managing the financial crisis is inevitable. To manage the impact of financial crises, understanding the dynamics of volatility spillover across various markets is imperative. This study has investigated the possible emergence of structural breaks in risk patterns after global financial crises in south Asian markets. Methodology - Using the data from July 2002 to June 2016, employing the Exponential GARCH methodology. Findings - This study finds a significant volatility spillover after the financial crisis of 2007-09. Therefore, the existence of a structural break in the risk pattern of south Asian capital markets cannot be fully rejected. Policy Implications - This conclusion is of prime importance to policymakers in devising policy guidelines concerning financial crises.